2021
DOI: 10.1021/acs.orglett.1c02117
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Halocyclizations to Access Benzoxazepinones and Benzoxazecinones

Abstract: We report a catalytic asymmetric halocyclization protocol to furnish benzoxazepinones and benzoxazecinones using (DHQ)2PHAL as the catalyst. Various halogenated benzoxazepinones and benzoxazecinones were achieved in excellent yields and enantioselectivities under mild conditions. A cocrystal structure of the substrate and the catalyst was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
(12 reference statements)
3
4
0
Order By: Relevance
“…17 Our previous study had reported a co-crystal structure of alkenoic acid-(DHQ) 2 PHAL, in which the carboxylic acid group of the substrate binds to the basic quinuclidine moiety of the (DHQ) 2 PHAL catalyst to give an acid-base adduct. 18 This observation is in alignment with a recent study by Borhan and co-workers in which a substrate-catalyst adduct was verified by NMR and computational studies. 19 When the (DHQD) 2 PHAL catalyst was treated with 1 equiv.…”
Section: Resultssupporting
confidence: 90%
“…17 Our previous study had reported a co-crystal structure of alkenoic acid-(DHQ) 2 PHAL, in which the carboxylic acid group of the substrate binds to the basic quinuclidine moiety of the (DHQ) 2 PHAL catalyst to give an acid-base adduct. 18 This observation is in alignment with a recent study by Borhan and co-workers in which a substrate-catalyst adduct was verified by NMR and computational studies. 19 When the (DHQD) 2 PHAL catalyst was treated with 1 equiv.…”
Section: Resultssupporting
confidence: 90%
“…The conformationally unbiased nature of these substrates is remarkable, filling a meaningful gap in the otherwise limited structure space pioneered by Tang 6 d and Yeung. 11 The technology also enables several 1,1-disubstituted alkene functionalization reactions, including epoxidation, that do not yet have more direct solutions despite the potential directing ability of the remote carboxylic acid. Essential to this success is the discovery that PIDA/I 2 is uniquely effective at generating the reactive iodonium species, one that engages the catalyst for productive and selective odolactonization.…”
Section: Discussionmentioning
confidence: 99%
“…6d Efforts by others provide context for the challenge, including halolactonization to benzofused 7-membered rings in up to 10% ee for iodolactonization, and 31% ee for bromolactonization. 10 Yeung recently reported enantioselective bromo-and chlorocyclizations that further generalize the use of an arylamine backbone, 11 prompting us to disclose our ndings. Importantly, all of these examples are limited to conformationally restricted unsaturated acids.…”
Section: Introductionmentioning
confidence: 96%
“…They have played an important role in asymmetric syntheses over the past many years because they are inexpensive, readily available, stable, and easily recoverable. As representative chiral ligands and chiral organocatalysts, dimeric Cinchona alkaloids via an ether bond with heterocyclic linkers have been widely used in catalytic asymmetric reactions such as asymmetric halogenations, Sharpless dihydroxylation, sulfenylation, allylic alkylation, and Michael addition. They have also been used to form C–C bonds, C–N bonds, and C–O bonds. As we know, the key step in chiral recognition is the formation of in situ diastereoisomeric complexes between enantiomers and a suitable chiral host. It is widely accepted that an effective chiral recognition model should involve multipoint interactions between the host and the guest, with the strongest and most effective interactions being electrostatic (Coulomb), hydrogen bonds, steric hindrance, π–π, and ion–dipole interactions .…”
Section: Introductionmentioning
confidence: 99%